Iran's Nuclear Ambitions - Chubin, Shahram (Book collections on Project MUSE., 2006)
"Iranian-born Shahram Chubin narrates the recent history of Iran's nuclear program and diplomacy, and argues that the central problem is not nuclear technology but rather Iran's behavior as a revolutionary state with ambitions that collide with the interests of its neighbors and the West"--Provided by publisher